Evolution of desire: a life of René Girard - Haven, Cynthia L. (Studies in Violence, Mimesis, and Culture Ser, 2018)
Intro -- Contents -- Chapter 1. Introduction -- Chapter 2. Magnetic North -- Chapter 3. Dark Times in the City of Light -- Chapter 4. Everything Is Possible -- Chapter 5. Mankind Is Not so Kind -- Chapter 6. The Pleasure of His Company -- Chapter 7. Everything Came to Me at Once -- Chapter 8. The French Invasion -- Chapter 9. Le SystÃ¨me-Girard -- Chapter 10. The Zero Hour of Culture -- Chapter 11. Lotus Land -- Chapter 12. The New Darwin of the Human Sciences -- Chapter 13. Who Asks about the Souls of These Men? -- Chapter 14. Terra Incognita -- Postscript: Hand in Hand -- Acknowledgments -- Chronology -- Notes -- Index